Solid Electrolytes: Extremely Fast Charge Carriers in Garnet‐Type Li6La3ZrTaO12 Single Crystals. Issue 12 (13th September 2017) - Stanje, Bernhard; Rettenwander, Daniel; Breuer, Stefan; Uitz, Marlena; Berendts, Stefan; Lerch, Martin; Uecker, Reinhard; Redhammer, Günther; Hanzu, Ilie; Wilkening, Martin
Abstract: The development of all‐solid‐state electrochemical energy storage systems, such as lithium‐ion batteries with solid electrolytes, requires stable, electronically insulating compounds with exceptionally high ionic conductivities. Considering ceramic oxides, garnet‐type Li 7 La 3 Zr 2 O 12 and derivatives, see Zr‐exchanged Li 6 La 3 ZrTaO 12 (LLZTO), have attracted great attention due to its high Li + ionic conductivity of 10 − 3  S cm − 1 at ambient temperature. Despite numerous studies focussing on conductivities of powder samples, only few use time‐domain NMR methods to probe Li ion diffusion parameters in single crystals. Here we report on temperature‐variable NMR relaxometry measurements using both laboratory and spin‐lock techniques to probe Li jump rates covering a dynamic time window spanning several decades. Both techniques revealed a consistent picture of correlated Li ion jump diffusion in the single crystal; the data perfectly mirror a modified BPP‐type relaxation response being based on a Lorentzian‐shaped relaxation function. The rates measured could be parameterized with a single set of diffusion parameters. Results from NMR are completely in line with ion transport parameters derived from conductivity spectroscopy. Abstract : The Li ions in single crystals of Li6 La3 ZrTaO12 are exposed to fast very fast exchange processes. The reason behind these fast hopping processes, which have been revealed by NMR spin‐lattice relaxometry, is an enhanced pre‐factor of the underlying Arrhenius relation that boosts ion dynamics above room temperature. The pre‐factor is, besides other factors, influenced by entropic contributions.